Hydroxyproline, a Serum Biomarker Candidate for Gastric Ulcer in Rats: A Comparison Study of Metabolic Analysis of Gastric Ulcer Models Induced by Ethanol, Stress, and Aspirin. Issue 9 (January 2014) - Takeuchi, Kenichiro; Ohishi, Maki; Endo, Keiko; Suzumura, Kenichi; Naraoka, Hitoshi; Ohata, Takeji; Seki, Jiro; Miyamae, Yoichi; Honma, Masashi; Soga, Tomoyoshi
Gastrointestinal symptoms are a common manifestation of adverse drug effects. Non-steroid anti-inflammatory drugs (NSAIDs) are widely prescribed drugs that induce the serious side effect of gastric mucosal ulceration. Biomarkers for these side effects have not been identified and ulcers are now only detectable by endoscopy. We previously identified five metabolites as biomarker candidates for NSAID-induced gastric ulcer using capillary electrophoresis–mass spectrometry (CE–MS)-based metabolomic analysis of serum and stomach from rats. Here, to clarify mechanism of changes and limitations of indications of biomarker candidates, we performed CE–MS-based metabolomic profiling in stomach and serum from rats with gastric ulcers induced by ethanol, stress, and aspirin. The results suggest that a decrease in hydroxyproline reflects the induction of gastric injury and may be useful in identifying gastric ulcer induced by multiple causes. While extrapolation to humans requires further study, hydroxyproline can be a new serum biomarker of gastric injury regardless of cause.